Economic valuation of carbon capture and storage in the puna dry of southwestern Peru - Medina, César E.; Medina, Yasmy K.; Bocardo, Edwin F. (Bosque (Valdivia), 2020)
In the face of a global warming scenario, carbon capture and storage has become an international strategy to mitigate the effect of greenhouse gases. Oceans and Tropical forests are considered the largest carbon sinks in the world, however a few studies have evaluated the relative importance of other plant formations as carbon sinks in the Neotropical Region. This study documents the economic value of carbon capture and storage by five plant formations representative in the Puna Seca of southwestern Peru. Sampling plots were established to estimate the biomass contained in seedlings of Pajonal, Tolar, Bofedal, Yaretal and Queñual, in Salinas y Aguada Blanca National Reserve (Arequipa, Peru). Later, carbon stored and carbon captured as CO2 was estimated. The Peruvian average carbon exchange price per ton of CO2 was used for the economic evaluation of environmental services. It was found that the Reserve contains at least 13,507,104.16 equivalent metric tons of CO2 worth U$D 86,310,395.58. Bofedal was the main vegetal formation that contributed in these values (52.48 %), in spite of being little represented in the total area of the Reserve (2.58 %). It is expected that the economic value obtained will serve as a frame of reference in decision-making for various purposes (environmental awareness, environmental management instruments, national accounting, among others).